Acceptance of open source software among UiTM students: a case study of diploma level Computer Science students in UiTM Johor / Yusnita Sokman, Ahmad Kamalrulzaman Othman and Hisham Md Basir - Sokman, Yusnita; Othman, Ahmad Kamalrulzaman; Md Basir, Hisham (2011)
This paper explores the issues of students' perception and acceptance level towards OSS among Diploma in Computer Science students. Furthermore, it is also to determine the potential factors that hinder students' perception and acceptance towards OSS and offer possible solutions to encourage the adoption of open source software in Malaysian computer science institutions. A total of 205 students from various classes and specialization fields were sampled. The overall results reveal that the students' exposure and acceptance is considerably average.